Globalised mission as opportunity - Jacobs, Pierre J. (HTS teologiese studies, 2015)
Globalisation develops at a staggering pace that envelopes and infiltrates local South African communities in various ways. Through technology a person can have access to anything today. Should the church try to keep up, or compete with such a reality? This article aims to encourage the church to develop a responsible missional character, which embraces the opportunities globalisation offers – to be a participative forum in a community comprising of more than religious people. Through re-evaluating the church’s missional intent, by shifting the paradigm away from self-centred outcomes, the church should contribute to such a community’s articulation of faith.